Awareness, knowledge and acceptance of community on a non-communicable disease intervention – findings from the “Healthy Community, Developed Nation” (KOSPEN) in the Southern Zone of Peninsular Malaysia - Lim, Hui Li; Chong, Siew Man; Heng, Pei Pei; Lim, Kuang Kuay; Sumarni Mohd Ghazali,; Kee, Chee Cheong; Lim, Jia Hui; Teh, Chien Huey; Lim, Kuang Hock (Penerbit Universiti Kebangsaan Malaysia, 2020)
Introduction Community-based health promotion programme has been recognised to reduce modifiable lifestyle risk behaviours for non-communicable diseases. The aim of this study was to evaluate the proportion of the awareness, knowledge and acceptance of a community-based intervention programme, “Komuniti Sihat, Pembina Negara“ (KOSPEN) (Healthy Community, Developed Nation). Methods This cross-sectional study employed a two-stage proportionate sampling method to select a representative sample of communities in the Southern states of Peninsular Malaysia, Negeri Sembilan, Malacca, and Johor. Face-to-face interviews by trained research assistants using pre-validated questionnaires was the study tool applied. Results The study revealed that approximately two thirds of respondents were aware of the KOSPEN programme (65.5%) and almost half (45.4%) of them were involved in the health promotion activities, namely health screenings (84.8%), health talks (66.4%), and providing plain water in formal occasion (52.9%). About two thirds and one-quarter of them have a very good (73.4%) and good (24.1%) general view on this programme. Four out of ten respondents faced difficulties joining the activities. Lack of time (83.0%) was reported as the main barrier. Conclusions The KOSPEN programme in overall was moderately accepted by the community. However, the need for future improvement has to be highlighted in order to enhance the involvement and participation of the communities.